2021
DOI: 10.5430/jnep.v11n5p46
|View full text |Cite
|
Sign up to set email alerts
|

Why should we care about academic integrity in nursing students?

Abstract: Integrity, honesty, and respect are essential values for nursing students. Yet, in recent years the rise of breaches in academic integrity has become alarming. The era of increasing advances in the capabilities of smart technologies may be facilitating rather than deterring students from academic integrity breaches in their work and assessments. This issue raises questions for nurse academics on how they can best ensure that nursing students align their behavior with the expected nursing’s professional values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Bultas et al [8] view the onus of AI as the responsibility of the educator. However, Emmanuel et al [4] found that academics have been found wanting in areas of AI, relating to the pres-Published by Sciedu Press sure felt when student evaluations are scrutinized. Hence more leniency may be shown when it comes to breaches in AI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bultas et al [8] view the onus of AI as the responsibility of the educator. However, Emmanuel et al [4] found that academics have been found wanting in areas of AI, relating to the pres-Published by Sciedu Press sure felt when student evaluations are scrutinized. Hence more leniency may be shown when it comes to breaches in AI.…”
Section: Discussionmentioning
confidence: 99%
“…[2] While Guerrero-Dib et al identified that introducing first-year nursing students to the values and practices of AI facilitates student achievement of high standards of excellence and learning [3] Emmanuel et al further recognised that early focus on AI can lead to students developing good ethical perspectives. [4] AI is an integral part of all university degrees. It is postulated that breaches in AI, in nursing, are increasing, especially with the increasing use of and reliance upon modern technology in the academic arena.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrity is a core expectation of professional nursing practice, with nurses highly regarded for their honesty and high ethical standards (Emmanuel et al 2021). Globally, nurses are often voted "the" most trusted profession in public confidence surveys, rating higher than doctors, dentists, police officers and schoolteachers (Gallup Inc 2020;Ipsos Reid 2018;Roy Morgan Research Ltd 2017).…”
Section: Introductionmentioning
confidence: 99%